Electronic Educational Games and its Relationship to Learning Motivation for Elementary School Students in E-Learning Platforms from Teachers’ Point of View - Abuabat, Daleen Abdullah; Almuhannna, Manal Abdulrahman (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the relationship between electronic educational games and the learning motivation of elementary school students in e-learning platforms from the teachers’ point of view, by identifying the level of teachers’ use of electronic educational games in e-learning platforms, and the level of learning motivation among students in e-learning platforms. To achieve the objectives of the study, the descriptive correlative method was used, and the sample consisted of (304) female elementary school teachers who were chosen by the snowball sampling method. Questionnaire was used as a tool for data collection. The results of the study showed that there is a significant positive correlation at the level (0.01) between the level of elementary school teachers’ use of electronic educational games in e-learning platforms, and the level of learning motivation among elementary school students in e-learning platforms, as the more practice of electronic educational games in e-learning platforms, the more motivated students to learn. Based on results, the study recommended doing research about the factors that limit the elementary school teachers from using the electronic educational games, and the importance of training and providing teachers incentives that support their use.
Keywords: Electronic Educational Games; Learning Motivation; E-Learning Platforms